Risk factors and novel prognostic score for predicting the 14-day mortality of severe traumatic brain injury patients - Nyoman Golden; Putu Eka Mardhika; Wayan Niryana; I Made Sukarya; I Putu Yuda Prabawa (DiscoverSys Inc., 2020)
Introduction: The mortality of severe traumatic brain injury (TBI) is contributed by the severity of the head injury, associated trauma, and complication during treatment. This study aimed to develop a prognostic scoring system of risk factors that contribute to the 14-day mortality of severe TBI.Methods: This was a prospective cohort study including 105 severe TBI patients recruited consecutively from March to October 2016. Multivariate analysis with logistic regression was performed to determine the most contributing risk factors. The validation of prognostic factor was performed with ROC, sensitivity and specificity analysis.Result: There were five significant risk factors of 14-day mortality, which were age > 60 years old (RR: 15.6, 95% CI: 1.88 – 129.95), hypoxia (RR: 17.78, 95% CI: 2.05 – 154.11), GCS 3 – 5 (RR: 34.71, 95% CI: 6.85 – 175.98), effacement of basal cistern (RR: 12.71, 95% CI: 2.61 – 61.95), and traumatic subarachnoid hemorrhage (tSAH) (RR:7.57, 95% CI: 1.19 – 48.36). The prognostic score ranged from 0 to 6 with the best cut-off point of 1. The best predictive AUC with ROC analysis was 0.817, 81.2% of sensitivity, and 75.0% of specificity.Conclusion: The proposed prognostic score has shown good predictive ability.